2017
DOI: 10.1186/s13034-017-0144-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic profiles and predictors of treatment outcome among children and adolescents attending a national psychiatric hospital in Botswana

Abstract: BackgroundAttention is currently being drawn to child psychiatric care, most especially in the developed countries. This type of care is still rudimentary in the developing countries. Botswana is one of the African countries with good health care services but mental illness is given the low priority. Child and adolescent mental health care (CAMHC) is almost non-existent likely due to the dearth of research which would drive a policy change in this direction. Hence the need for this research as a step towards e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…• Current challenges include difficulties with obtaining reliable estimates of the prevalence of BD in Botswana, including BP-II, in order to guide future strategies. Currently, national statistics records only show a broad diagnosis of BD, and even recent studies do not make a distinction between BP-I and BP-II [216,217]. • In addition, since initial diagnosis and treatment of most patients with mental disorders in Botswana, including those with BP-II, is carried out by psychiatric or general nurses, and there are currently no national STGs for the management of BP-II, there is a high probability of missing an accurate diagnosis.…”
Section: Botswanamentioning
confidence: 99%
“…• Current challenges include difficulties with obtaining reliable estimates of the prevalence of BD in Botswana, including BP-II, in order to guide future strategies. Currently, national statistics records only show a broad diagnosis of BD, and even recent studies do not make a distinction between BP-I and BP-II [216,217]. • In addition, since initial diagnosis and treatment of most patients with mental disorders in Botswana, including those with BP-II, is carried out by psychiatric or general nurses, and there are currently no national STGs for the management of BP-II, there is a high probability of missing an accurate diagnosis.…”
Section: Botswanamentioning
confidence: 99%
“…Likewise, the nature of the sample used (hospital record review) and the small sample size may have contributed to the higher rate (25%) of ADHD reported from an earlier study in Botswana. 17 …”
Section: Discussionmentioning
confidence: 99%
“…The need to improve on perinatal care and discourage unplanned home delivery cannot be overstressed in this community, especially that an earlier study in Botswana had suggested a link between perinatal complications and childhood mental disorders. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these policies, the diagnosis of ASD at early ages of development has been more frequent, however, there are still some regional imbalances between different areas of the country (BRASIL, 2007, BRASIL, 2014, PORTOLESE et al, 2017. These imbalances are associated with different factors, such as a lack of training of health professionals and a shortage of specialized services (COUTO et al, 2008;SANTOS & FERNANDEZ, 2014;BORDINI et al, 2015;SANTOS & CELERI, 2018); delays in parents detecting the first signs of autism that in turn delays the search for professional help and receiving the diagnosis (ZANON et al, 2014;OLASHORE et al, 2017); and the long waiting times for diagnostic evaluations in specialized child mental health services (ARAUJO & TANAKA, 2012), among others. The diagnosis of ID in early life has not received the same attention as ASD in terms of studies that assess the factors associated with the delay in its identification (RUSSELL et al, 2019).…”
Section: Introductionmentioning
confidence: 99%